PROBLEM OF MISTAKES IN DATABASES, PROCESSING AND INTERPRETATION OF OBSERVATIONS OF THE SUN. II. SOLAR FLARES - Lozitska, N. I. (Одеські астрономічні публікації, 2016)
The contribution of space-based observations of solar flares in the database for the past 50 years has increased significantly, almost completely replacing the ground observations. The statistical parameters of the temporal distribution of solar flares, obtained using ground-based and space-based observations, differ significantly. We investigated the reasons for these differences to be taken into account in the study of flare activity of the Sun in the solar activity cycles 21-24.